Joints and shear zones as indicators of principal stress in the area around Bainoli, district Chamoli, Lesser Garhwal Himalaya, India - Singh, R. A.; Gairola, V. K. (Journal of Nepal Geological Society, 1998)
The orientation of joints and shear planes have been measured in the rocks around Bainoli, district Charnoli, U.P. For the stress analysis, the area has been divided into 17 subareas with respect to joints and 7 subareas with respect to shear planes. 100-sector rose diagrams reveal four joint sets in the area, which strike in NW-SE, N-S, NE-SW and E-W directions with a variation of upto 10° in different subareas. Only the NW-SE set is prominent and common to all the subareas. Four sets of the shear planes have been recognised in the area striking in N50°W-S50°E, N-S, N40°E-S40°W and E-W. Of these, two sets are prominent in which one strikes N50°W-S50°E and other strikes N40°E-S40°W with a local variation of upto 10° in different subareas. The analysis of joints and shear planes reveals that joints were mainly developed during the second phase of deformation and shear planes were mainly developed during the third phase of deformation. In the later phases of deformations, earlier joints/shear planes were reactivated and reoriented, as well as new joints/shear planes were also developed. Thus, different orientation of joints and shear planes are observed in the area. The principal stress directions have been also inferred during the second and third phases of deformations with the help of joints and shear zones, respectively.